Resultado primário e contabilidade criativa: Reconstruindo as estatísticas fiscais "acima da linha" do governo geral - Sérgio Wulff Gobetti; Octávio Orair (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This Discussion Paper presents an overview of Brazilian public finances through a meticulous work of adjusting and consolidating fiscal statistics, in which central government data were adjusted to deal with creative accounting and subsequently consolidated with data from subnational governments. The result is new monthly estimates of the general government's "above the line" primary balance for the period from January 2002 to April 2016. The analysis based on these fiscal series rejects the hypothesis that the recent deterioration of primary balances was generated by deeper fiscal expansion through expenditures. It can, however, be said that subsidies played a prominent role in recent fiscal expansionism, alongside with tax exemptions, and that this change in the fiscal policy mix - in lieu of public investment - might have been ineffective to sustain growth economic, as well as presented a high fiscal cost.
Keywords: E62; H6; H72; 330; creative accounting; fiscal expansion; primary balance